Evaluation Of the Legality and Requirements of Starlink in Indonesia Using a Regulatory Impact Analysis Approach - Ficco Clivano Ikhsan; Gunawan Wibisono (Universitas Indonesia, 2026)
Indonesia has a territory and large population. Indonesia is one of the largest countries in the world, with an internet penetration rate of around 79% of the total population as of 2024. This has prompted Indonesia to improve its network and other telecommunications-related issues. This study evaluates the feasibility of utilizing Starlink satellites to equalize telecommunications access in Indonesia. Based on Law No. 36 of 1999 concerning Telecommunications, which mandates the provision of services to all regions, this study aims to evaluate the role of Starlink while identifying legal and regulatory obstacles related to this new technology. It also analyzes the legality of this technology and explains the sovereignty issues raised by Starlink. By applying the Regulatory Impact Analysis method, which uses the main stages of problem definition, policy identification, impact and policy evaluation, stakeholder consultation, and selection of alternative policies through interviews and framework. It began with the first option, which was a policy where the government permanently revokes Starlink's operational licenses to prioritize national sovereignty and data security. Option 2 approaches the issue with a temporary suspension and a comprehensive technical audit of the Network Operation Center (NOC) and Lawful Interception capabilities, and option 3 focuses more on giving Starlink more time to fully comply with regulations. Option 2 is the best choice because of its highest PMI score and its ability to balance the interests of regulators, operators, and the public. However, it temporarily disrupts service access for potential users, particularly in remote regions.